2013
DOI: 10.1161/circimaging.112.000333
|View full text |Cite
|
Sign up to set email alerts
|

T1 Measurements Identify Extracellular Volume Expansion in Hypertrophic Cardiomyopathy Sarcomere Mutation Carriers With and Without Left Ventricular Hypertrophy

Abstract: Background Myocardial fibrosis is a hallmark of hypertrophic cardiomyopathy (HCM) and a potential substrate for arrhythmias and heart failure. Sarcomere mutations appear to induce profibrotic changes before left ventricular hypertrophy (LVH) develops. To further evaluate these processes, we used cardiac magnetic resonance (CMR) with T1 measurements on a genotyped HCM population to quantify myocardial extracellular volume (ECV). Methods and Results Sarcomere mutation carriers with LVH (G+/LVH+, n = 37) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
3
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(169 citation statements)
references
References 48 publications
13
145
3
8
Order By: Relevance
“…In addition, recent studies have showed the presence of myocardial fibrosis in subjects with pathogenic sarcomere mutations and no LV hypertrophy, [13,14] supporting the hypothesis that fibrotic remodeling is triggered early in HCM pathogenesis.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, recent studies have showed the presence of myocardial fibrosis in subjects with pathogenic sarcomere mutations and no LV hypertrophy, [13,14] supporting the hypothesis that fibrotic remodeling is triggered early in HCM pathogenesis.…”
Section: Introductionmentioning
confidence: 78%
“…Both shorter post-contrast myocardial T1 times [49] and increased ECV [14]. both indexes of diffuse myocardial fibrosis, correlate with non-invasively estimated LV filling pressure, suggesting a mechanistic link between diffuse myocardial fibrosis and abnormal diastolic function in HCM.…”
Section: T1-mappingmentioning
confidence: 89%
See 1 more Smart Citation
“…[21][22][23] CMR has added to these insights by demonstrating that a number of additional morphological abnormalities may be present including myocardial crypts (see Figure 1F), elongated mitral valve leaflets, expanded extracellular space (with T1 mapping) and LGE. [24][25][26][27] When genetic testing is negative or ambiguous (as in 60 % of patients), or when not pursued due to financial or personal preference, CMR can identify these abnormalities in the absence of LV hypertrophy, raising suspicion for genotype-positive status among family members. 2,21 This should prompt continued close surveillance with serial CMR for development of LV hypertrophy and conversion to clinical disease.…”
Section: Assessment Of Family Members With Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…In addition, conflicting data exist regarding T1 mapping values in G+P-patients, and if this value can indeed differentiate G+P-patients to normal controls. 24,50 Thereby, continued investigations applying T1 mapping to HCM is necessary to better to define the role of this technique.…”
mentioning
confidence: 99%